2022
DOI: 10.1590/0001-3765202220201425
|View full text |Cite
|
Sign up to set email alerts
|

Helminth endoparasites of endemic fish Pygocentrus piraya (Characiformes, Serrasalmidae) from Três Marias reservoir, Minas Gerais, Brazil

Abstract: Ten endoparasite species found in Pygocentrus piraya, which is a piranha species native to São Francisco river, were collected from 108 fi sh caught in Três Marias reservoir in 2004 and 2005, namely: Digenea -Austrodiplostomum sp. (metacercariae); Eucestoda -Proteocephalidae gen. sp. (plerocercoids); and Nematoda -Procamallanus (Spirocamallanus) inopinatus, Cystidicoloides fi scheri and Capillostrongyloides sentinosa (adults); Spinitectus rodolphiheringi (juvenile); Hysterothylacium sp., Contracaecum sp. Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The present study is the first report of the larval stage of the genus in Australia, which shows the role of a native fish, southern pygmy perch, in its life cycle. According to Santos-Clapp et al (2022), Spiroxys larvae have a higher incidence in smaller fish. Fish may acquire the infection by eating infected first intermediate hosts or paratenic hosts, such as copepods, aquatic insects and molluscs (Moravec 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The present study is the first report of the larval stage of the genus in Australia, which shows the role of a native fish, southern pygmy perch, in its life cycle. According to Santos-Clapp et al (2022), Spiroxys larvae have a higher incidence in smaller fish. Fish may acquire the infection by eating infected first intermediate hosts or paratenic hosts, such as copepods, aquatic insects and molluscs (Moravec 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The endoparasitic fauna of P. piraya from the upper São Francisco River, in the Três Marias reservoir, Minas Gerais, was studied by Santos-Clapp et al (2022) and no pentastomid specimens were found. The presence of Sebekia sp., now recorded in P. piraya from the same basin, but originating from marginal lagoons, indicates that the characteristics of these sites favor ingestion of sebekid eggs by piranhas, possibly due to closer contact between these intermediate hosts and crocodilians, i.e.…”
Section: Discussionmentioning
confidence: 99%